Examining Multitasking Performance in Naturalistic 2D Environments. (September 2022) - Jackson, Kenneth M.; Melles, Lydia; McCarty, Madeleine M.; Shaw, Tyler H.; Helton, William S.
Visual searches are done frequently and commonly while doing other tasks. Previous research has shown that multitasking inhibits performance of tasks done together, however little has examined visual search and word recall performed together, especially when there are an undisclosed number of targets to be found. The purpose of this study is to examine how multitasking affects visual search and word recall. Participants recalled words shown on a heads-up display while simultaneously searching realistic landscape images for target distortions. The participants also completed these tasks individually. It was found that during multitasking, participants found significantly less targets and remembered significantly less words than when doing those tasks individually. It was also shown that prioritizing tasks led to small improvements in performance for that task. The results of this study could be used to influence design of technology made for individuals searching environments who also need to communicate information.